Analisis Pelaksanaan Supervisi Klinis Pada Kebijakan Pembatasan Keterlibatan PPDS Level 1 Di RS X Medan - Hasibuan, Rapotan; Pulungan, Dea Rizka Ananda; Syahfitri, Dewi; Adelia, Difa; Hasibuan, Ayu Cahaya; Salsabila, Rizka Fauziah (Yayasan Jompa Research and Development, 2025)
The involvement of early-stage students (Level 1 PPDS) in emergency services often creates a dilemma between the need for learning and the demands of service efficiency. Therefore, a teaching hospital (RS X) implemented a policy limiting the involvement of Level 1 PPDS in the Emergency Department (ER) to maintain patient safety and service quality. This study aims to examine the implementation of this policy and its impact on the clinical learning process and the workload of medical personnel. The method used was qualitative descriptive through in-depth interviews and observations with the Head of the Emergency Department (UFP), Head of the ER, DPJP, and PPDS. Data were analyzed thematically to identify patterns in the experiences and perspectives of the informants. The results showed that this policy increased the effectiveness and safety of services, but also limited direct practical experience for Level 1 PPDS and increased the supervisory burden for senior PPDS and DPJP. Nevertheless, the implementation of the principle of staged responsibility and close supervision still supported safe and directed clinical learning. Overall, this policy is considered effective in maintaining a balance between service and education, although it needs to be balanced with strengthening the supervision system and simulation-based learning to maintain the quality of clinical education.